High-dose short-term creatine supplementation without beneficial effects in professional cyclists: a randomized controlled trial - David Barranco-Gil; Lidia B. Alejo; Carlos Revuelta; Miguel Górriz; Itziar Pagola; Laureano M. Ozcoidi; Alejandro Lucia; Pedro L. Valenzuela (Taylor & Francis Group, 2024)
ABSTRACTBackground Growing evidence supports the ergogenic effects of creatine supplementation on muscle power/strength, but its effects on endurance performance remain unclear. We assessed the effects of high-dose short-term creatine supplementation in professional cyclists during a training camp.Methods The study followed a double-blind, randomized parallel design. Twenty-three professional U23 cyclists (19 ± 1 years, maximum oxygen uptake: 73.0 ± 4.6 mL/kg/min) participated in a 6-day training camp. Participants were randomized to consume daily either a recovery drink (containing carbohydrates and protein) with a 20-g creatine supplement (creatine group, n = 11) or just the recovery drink (placebo group, n = 12). Training loads and dietary intake were monitored, and indicators of fatigue/recovery (Hooper index, countermovement jump height), body composition, and performance (10-second sprint, 3-, 6-, and 12-minute time trials, respectively, as well as critical power and W') were assessed as study outcomes.Results The training camp resulted in a significant (p < 0.001) increase of training loads (+50% for total training time and + 61% for training stress score, compared with the preceding month) that in turn induced an increase in fatigue indicators (significant time effect [p < 0.001] for delayed-onset muscle soreness, fatigue, and total Hooper index) and a decrease in performance (significant time effect [p = 0.020] for critical power, which decreased by −3.8%). However, no significant group-by-time interaction effect was found for any of the study outcomes (all p > 0.05).Conclusions High-dose short-term creatine supplementation seems to exert no consistent beneficial effects on recovery, body composition or performance indicators during a strenuous training period in professional cyclists.